Manual de orientação para uma plataforma de força experimental por meio de identificação de fatores críticos de usabilidade - Reis, Wasington Almeida (2016)
Many unintuitive medical equipment and difficult learning have not instructive documents nor satisfactory usability, which may cause erroneous operations Thus, the force platform studied considered experimental, is without any formal standardize their usage processes that can support future provisioning users. Therefore, the aim of this study was to propose a guidance manual for use of the experimental force platform by identifying critical factors of usability, so you can help users carry out the assessment of safe and efficient postural control. The study was conducted in Strategic Technologies Center for Health (NUTES) in conjunction with the Motor Behavior Laboratory (LACOM), Department of Physical Education at the State University of Paraiba, in Campina Grande - PB. The population and sample of this research were composed of 10 individuals, professionals and students of Physical Education and Physiotherapy of both sexes. For the collection of information was carried out a pilot study of the use of process equipment. Also, we used an adapted form of the standard NBR IEC 62366: 2010 which deals with issues related to equipment for health associated with usability, to identify technical features of the experimental force platform. Later we used a list of questions for the interview with users using equipment often in research. Finally, an observational test usability, to list the actions of users and the questionnaire "Questionnaire for User Interaction Satisfaction - WANTED a score from 0 to 9 points, in order to assess the user's impression regarding interaction system, in which the means of questions and suggestions points showed improvements equipment. All stages of this study, to base the construction of the guidance manual, whose main purpose assist in learning and minimize usability errors when using the specific force platform.